Final answer:
The solution to the system of equations -3x-2y=-4 and 9x+3y=15 is found by using the elimination method, resulting in x = 2 and y = -1.
Step-by-step explanation:
The solution to the system of equations given by:
- -3x - 2y = -4
- 9x + 3y = 15
can be found using several methods, such as substitution or elimination. In this situation, the elimination method might be the simplest since the coefficients of x in both equations are multiples of each other. The steps are as follows:
- Multiply the first equation by 3 to make the coefficients of x in both equations the same in magnitude but opposite in sign.
- Add the modified first equation to the second equation to eliminate x.
- Solve the resulting single-variable equation for y.
- Substitute the value of y back into one of the original equations to solve for x.
Following these steps:
- Multiply the first equation by 3:
- (-3x - 2y) * 3 = -4 * 3
- -9x - 6y = -12
Add the modified first equation to the second:
- -9x - 6y + 9x + 3y = -12 + 15
- -3y = 3
Divide by -3 to solve for y:
Substitute y = -1 into the second original equation:
- 9x + 3(-1) = 15
- 9x - 3 = 15
- Add 3 to both sides:
- 9x = 18
- Divide by 9:
- x = 2
The solution to the system of equations is x = 2 and y = -1.